Analisis Wacana Kekerasan Seksual Terhadap Perempuan dalam Film "Demi Nama Baik Kampus" dan Film "Please Be Quiet" - Mulyani, Try; Handriyotopo, Handriyotopo; Rustim, Rustim (Rekam, 2023)
This study discusses the discourse of sexual violence in the short film Demi Nama Baik Kampus and the short film Please Be Queit to find out the representation of women as victims of sexual violence in the film. This study uses qualitative methods and Sara Mills' critical discourse. Based on its form, critical discourse analysis is divided into 3, namely the position of the subject-object and the position of the reader by selecting scenes that are considered representative. The findings of the analysis show that the position of the subject is carried out by a female character named Sinta who is a victim of sexual violence by her supervisor in the campus environment in the short film For the Good Name of the Campus. Whereas in the short film Please Be Queit played by Sarah who is considered a victim of sexual violence in the work environment. The position of the object is described as an actor that supports the subject's motion. Meanwhile, the writer positions Sarah and Sinta as parties who confirm the incident, so that the text is from the point of view that Sinta and Sarah experienced. The reader's position cannot change the discourse written by the author, because the reader cannot provide arguments to the writer, if there is no discrepancy in the content of the film's discussion.